Tuberculous abscess on the chest wall - Ayık, S.; Çakan, A.; Aslankara, N.; Özsöz, A. (Monaldi Archives for Chest Disease, 2016)
A 58-year old patient on dialysis for four years due to chronic renal failure presented with complaints of painless, continuously growing swelling on the left of his back and coughing, symptoms evolving over a period of approximately 3 months. Physical examination revealed a soft fixed mass of 10 x 10 x 4 cm on the left infrascapular area on the chest wall. The sample taken from the inflammation on the chest wall was analyzed with PCR method which resulted positive for Acid Fast Bacilli (AFB), tissue biopsy showed dermatitis with granulomata and sputum was positive for AFB. Thoracic MR, performed for the purpose of detecting the relationship between the lesion on the lung and the one on the chest wall, detected changes in the inflammatory soft tissues and multiple small abscess formations on the chest wall. There was no pathological signal in the bone structures of the chest wall. This case underlines the necessity to include “Empyema necessitatis’’ in the preliminary diagnosis when there is a soft tissue swelling on the chest wall without inflammatory signs in patients with reduced immune defences.